Multi-hazard Risk Configurations: A Search for Common Patterns in Three Latin American Cities During COVID-19 - Jiménez Barboza, Gustavo Adolfo (2022)
COVID-19 has seriously affected urban populations worldwide. It comprises a disaster category that accompanies more recurrent or familiar expressions associated with earthquakes, flooding, landslides, subsidence and tsunamis. Despite the differences in these hazard types, the expressions of vulnerability and exposure and their causes are often similar and many of these are based on pre-existing everyday living conditions. The present article provides preliminary evidence and analysis from the social and territorial incidence of COVID-19 to help confirm the now increasingly argued hypothesis that susceptible populations and areas are often the same, independent of the hazard type. It argues for more integral, livelihood and development-informed approaches to disaster risk management, based primarily on vulnerability and exposure reduction and control.